Species composition, abundance and distribution of surface plankton in Panabolon Island, Nueva Valenciana, Guimaras. - Ladica, Maritess Nacionales (1999.)
A three-month study of the composition abundance and distribution of surface plankton in Panabolon Island, Nueva Valencia, Guimaras was conducted from December, 1998 to February, 1999. Density, abundance and similarity indices between time intervals and months were also computed. Physico-chemical parameters - temperature, salinity and water transparency - were montiored every month. (p)A total of 2 phyla, 2 classes, 3 orders, 4 families, 26 genera, and 42 species for the phytoplankton were recorded and 5 phyla, 6 classes, 8 orders, 6 families, 10 genera, and 10 species for the zooplankton. (p)Predominant phytoplankton species during the study were diatoms and copepods respectively. For diatoms, the most abundant species was Amphora sp. followed by Navicula sp. and then Nitzchia sp. The copepod group, on the other hand, was predominated by Cyclops sp., then by Oithona sp., and by Calaus sp. (p)Phytoplankton were more dense and diverse during daytime samplings while for zooplankton the same parameters were highest during nightime. Highest density was noted in December and subsequently decreased in the next two months (Dec: D=135.98; jan: D=86.06; Feb: D=31.64). (p)Diversity was highest during the months of December and January for phytoplankton and zooplankton respectively. Zooplankton diversity was highest in January during the 3 AM sampling for all three months least diversity was during the month of February and during 9 AM sampling time. The months of January and February at 3 PM had the most similar phytoplankton composition while it was December and January at 3 AM for zooplankton.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Plankton -- Panabolon Island -- Nueva Valencia, Guimaras